Letter from James A. Healy to Mrs. [Áine] Ceannt thanking her for four copies of her book on the Irish White Cross and describing the holdings of the collection of Irish History at the Hoover Institution on War, Revolution, and Peace, - Healy, James Augustine, 1891-1975 (1948)
Healy mentions the collection of Irish History at the Hoover Institution on War, Revolution, and Peace holds "Dr. Oliver Gogarty's personal copy of Ireland's 1916 Declaration of Independence" and asks for any material that Áine might have.